LA INCONGRUENCIA EXISTENTE EN LA LEGISLACIÓN ECUATORIANA AL ESTABLECER LA CAUSAL DE DIVORCIO CUANDO SE ENCUENTRA LA RESPONSABILIDAD DEL AGRESOR EN LA LEY CONTRA LA VIOLENCIA A LA MUJER Y LA FAMILIA Y LAS DISPOSICIONES QUE ESTABLECE EL CÓDIGO CIVIL ECUATORIANO - Chamba Pesantes, Ángel Tadeo (2015)
3 2.1 ABSTRACT This thesis aims, scientist, study and propose a solution to the problem of research as is "INCONGRUITY IN LEGISLATION ECUADOR TO ESTABLISH THE CAUSE OF DIVORCE WHEN THE RESPONSIBILITY OF THE OFFENDER IN THE LAW AGAINST VIOLENCE IS THE WOMEN AND THE FAMILY, AND THE PROVISIONS ESTABLISHING THE ECUADORIAN CIVIL CODE " which I consider very important to analyze in detail the rules, in Ecuador and in other countries. The disintegration of the home since ancient times has generated violence between cohabitants or partners, forth treason I do a doctrinal study to realize from the origin of the family and its evolution to the present. The collection of both theoretical, doctrinal, legal information and comparative law; the study of the Constitution of the Republic of Ecuador in force, international treaties and conventions, the Civil Code and the Law Against Violence to Women and the Family; analyzing surveys and interviews with Lawyers in free practice give me the reason that there is inconsistency between Law 103 and Ecuador's Civil Code, as to the penalties provided in Art. 22 of the Law and the grounds for divorce of Article 110 of the Civil Code; I so propose this research work, to establish improvement the same legal body. ”